Modulating Effects of Landscape Characteristics on Responses to Warming Differ Among Butterfly Species - Hellegers, Marjon; van Swaay, Chris A. M.; van Hinsberg, Arjen; Huijbregts, Mark A. J.; Schipper, Aafke M. (Frontiers in Ecology and Evolution, 2022)
Understanding and predicting biodiversity responses to climate change are vital to inform conservation strategies, but this is not straightforward as climate change responses depend on the landscape context and differ among species. Here, we quantified changes in the distribution and abundance of 30 butterfly species in the Netherlands in relation to climate change and in landscapes that vary in the amount and connectivity of (semi-)natural vegetation (SNV). We obtained yearly counts of well-monitored butterfly species from 327 time series over 27 years (1992-2018). We used these counts to build mixed effect hurdle models to relate species’ occurrence and abundance to temperature and the amount and connectivity of SNV around the sites. For 55% of the butterfly species, an increased amount or connectivity of SNV corresponded with stronger increases or reduced decreases in occurrence in response to warming, indicating that SNV may facilitate range expansion or mitigate extirpations due to climate change. However, for the occurrence of the other species we found no or a negative interaction between warming and SNV. Further, we did not find indications of a mitigating effect of SNV on abundance responses to warming. Our results thus suggest that increasing the amount and connectivity of SNV does not offer a ‘one-size-fits-all’ solution, highlighting the need for additional measures if butterfly diversity is to be conserved.